FENOMENA GASLIGHTING SEBAGAI BENTUK PENINDASAN KEPERCAYAAN DIRI ANAK - Fitrianingtyas, Anjar; Pradista, Alvindio Yoga; Nurjanah, Novita Eka (FKIP UNILA, 2024)
Gaslighting is a behavior that aims to manipulate, initimidate the victim, laugh at and belittle the victim's feelings, and say that everything that happens victim's fault in order to disrupting his sanity and belief in themself. The purpose of this study was to determine the phenomenon of gaslighting as a perform of suppression of children's self-confidence through the experience of the research subject. This research design uses a qualitative phenomenological approach developed by Van Kaam. The research subjects was taken using purposive sampling technique, there were 5 parents who have 5 years old children and 1 expert. The research data were obtained through interviews, field observation, and documentation. The results showed that parents unconsciously gaslighted their children in their daily activities which made children often feel unsure of their abilities and feel guilty for something they did not do. This suggest that education about gaslighting still needs to be disseminated.